MEDIA PEMBELAJARAN VIDEOSCRIBE BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK SISWA KELAS IV SD - Nicanta, Flower; Wibawa, I Made Citra; Dharmayanti, Putu Ary (Pascasarjana Universitas Pendidikan Ganesha, 2025)
The use of engaging, contextually relevant learning media appropriate to the learning characteristics of elementary school students remains limited. There is a need for innovative, interactive learning media to support a contextual, meaningful learning process. This study aims to develop a VideoScribe-based learning media, combined with the Contextual Teaching and Learning (CTL) approach, to improve learning effectiveness among fourth-grade elementary school students. The method used in this study is the Research and Development method, which uses the ADDIE development model and includes the following stages: analysis, development, implementation, and evaluation. Data collection uses tests, observations, and interviews. The subjects in this study were 21 fourth-grade elementary school students. The analysis technique uses quantitative analysis. The results of the development show that the designed VideoScribe media is highly feasible, as validated by material and media experts and evidenced by positive responses from teachers and students. A limited trial in fourth grade showed that this media increased student engagement and understanding of the subject matter. The conclusion of this study shows that VideoScribe-based learning media integrated with the CTL approach is effective for use in elementary school students' learning. This finding implies that the development of technology-based media aligned with a contextual learning approach can be an alternative strategy for improving the quality of learning processes and outcomes, and can serve as a reference for teachers and media developers in creating more engaging and meaningful learning experiences.